COMPETITION LAW IN THE EU - Marina Corina JIPA (Challenges of the Knowledge Society)
The competition policy and norms in the European Union are a vital part of the internal market. Competition, although it is an element whose existence is essential for the proper functioning of the market, can be seen as an element of pressure on companies in trying to offer consumers a variety of products at the lowest possible prices. European Union competition policy has, at its disposal, a set of tools to protect against anti-competitive practices. The purpose of this paper is to analyse how anticompetitive policy is implemented in the European Union. This essay aims to understand the way in which the European Union is treating anti-competitive practices, addressing the various illegal issues, as well as the exceptions and their conditions. In the case of defining legal terms, the interpretations offered in the case law of the Luxembourg Court will be used. An assessment of the European Union's purpose and objectives with regard to protecting against anti-competitive practices is also an indicator of the implementation of the policy in this area. The paper will analyse the legal instruments and the way in which the Commission applies these instruments of protection against anti-competitive practices in order to restore the competitive conditions, by correcting the inappropriate practices of the enterprises. The results of the interaction between anti-competitive practices (agreements and abuse of a dominant position) and unfair trade practices (including dumping and subsidisation) will be discussed to understand the effectiveness of legal instruments in practice.